A Case of Subcortical Band Heterotopia Presented with Epilepsy and Speech Regression - Mahmud, Reaz; Gias Uddin, Kazi Mohammad; Rassel, Mohammad Aftab (Bangladesh Journal of Neuroscience, 2019)
Subcortical Heterotopia is a rare developmental disorder of human brain due to mutation in the DCX or LIS1gene.It is predominantly a disease of female. It usually present with refractory seizure and varying degree of mental retardation. Here a case of 22 years lady who presented with refractory seizure is reported. Her MRI revealed Double cortex and her EEG revealed Frontal intermittent rhythmic delta activity (FIRDA). Bangladesh Journal of Neuroscience 2019; Vol. 35 (2): 115-118